Comparison of the physiological responses and time-motion characteristics during football small-sided games: effect of pressure on the ball - Chen, Xiaohu; Zheng, Rui; Xiong, Bo; Huang, Xiaoling; Gong, Bingnan (Frontiers in Physiology, 2023)
This study aimed to compare the effects of pressure on the ball on physiological responses and time-motion characteristics during football small-sided games (SSG) between elite youth male players. 56 elite male youth football players (age:15.43±0.52 years) performed a 2+GK vs 2+GK game on a 30m15m pitch area with two playing conditions: 1) free play (FP), the player has no limitation to play; 2) pressure on the ball (PB), the player has directly and aggressively closed down space (located within 1.5 m) between themselves and the opposition player with the ball and can compete for possession. The percentage of time spent in different maximum heart rate (HRmax) zones, mean heart rate, blood lactate acid concentration, total distance covered, distance covered in 3 speed zones (sprint, high speed, moderate speed), number of high speed runs, number of sprint runs, top speed, number of direction changes, and ball recovery time were monitored. We found very significantly higher number of high speed runs (P<0.001; ES=1.154), number of direction changes (P<0.001; ES=2.347), ball recovery time (P<0.001; ES=3.529), percentage of time spent in 90%-100% HRmax (P<0.001; ES=3.033), mean heart rate (P<0.001; ES=1.940), blood lactate acid concentration (P<0.001; ES=2.245) and significantly higher high speed running distance covered (P=0.004; ES=0.520) in the PB condition. Conversely, the FP condition showed very significantly higher moderate speed running distance covered (P<0.001; ES=1.814) and significantly higher percentage of time spent in 80%-90% HRmax (P=0.012; ES=0.440). No significant differences were revealed on sprint running distance covered (P=0.407; ES=0.140), number of sprint runs (P=0.103; ES=0.279), top speed (P=0.130; ES=0.258) and percentage of time spent in 60%-70% HRmax (P=0.106; ES=0.276), 70%-80% HRmax (P=0.358; ES=0.155). We found that pressure on the ball had a substantial impact on the intensity of training, as evidenced by a significantly increased high speed running performance, number of directional changes, percentage of time spent at 90%-100% of maximum heart rate, mean heart rate, and blood lactate acid concentration. Additionally, ball recovery time decreased significantly.